THE POETICS OF SILENCE AND UNSPOKEN EMOTIONS IN AMERICAN PSYCHOLOGICAL NOVELLAS - Boltaeva Dilfuzaxon Shuxrat qizi (International Journal of Literature and Language Studies, 2026)
Abstract. This article examines the poetics of silence and unspoken emotions in American psychological novellas through a comparative analysis of Sherwood Anderson, Ernest Hemingway, and John Steinbeck. The study investigates how silence functions as a narrative strategy for expressing psychological conflicts, emotional repression, and interpersonal alienation. Drawing upon narratology, psychological criticism, and modernist literary theory, the research explores the role of subtext, omission, and indirect communication in shaping character consciousness. The methodological framework combines comparative-literary, narratological, and textual analysis. The findings demonstrate that silence serves not merely as the absence of speech but as a significant artistic device that conveys hidden emotions and psychological tension. Anderson employs silence to reveal loneliness and isolation, Hemingway utilizes subtext through his “Iceberg Theory,” and Steinbeck uses silence to expose social and emotional conflicts. The study concludes that the poetics of silence constitutes one of the defining features of the American psychological novella and contributes to the development of modern narrative techniques.